Sentiment Amongst the Customers of Touroperators After Terrorist Attack – Analysis of Social Networking Sites - Moroz, Mirosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Tunisia constitutes one of basic directions of tourist trips in Poland. However terrorist attack on the museum in Bardo, widely related in mass media, changed the image of Tunisia as the safe holiday destination. The assassination caused a number of consequences for the Polish tourism, for tour operators sending tourists to Tunisia, and finally for visitors (or intended to visit Tunisia). One of the key decisions of clients who bought stay in Tunisia, was a decision: to go or not to go there. In turn for people who just spent holiday in Tunisia, there’ another dilemma – to come back now or wait until the end of their stay. Similar decisions arose before the touroperators. From a sociological point of view, the social sentiment of opinions on outbound tourism to Tunisia reflect company profiles on Facebook (fanpage) of the principal tourist agencies sending customers to the country concerned. The fanpages were in fact sometimes very emotional discourse on line touroperator–client. The aim of the paper is to examine and evaluate the sentiment of statements on fanpages of main tour operators focusing around the question: to go or not to go there (tourist point of view); to continue departures or to cease them (point of view of touroperators). Because of the direct, immediate and honest (sometimes painfully) discussions conducted at company profiles on Facebook, you can glimpse into the motivations of choice for consumers on the one hand, and on the other take a look at and consider the arguments of travel operators.